Community Participation In Wetland Conservation In Nepal - Shrestha, Utsala (Journal of Agriculture and Environment, 2013)
Community participation plays vital role in the development of capacity for the management and utilization of their resources in sustainable way. There are ample success stories for proper management of common property resources through community management. Wetland resources are widely used by the local communities for their sustenance and economic well-being. In such case, local participation is effective tool for establishing an ecologically balanced use of available land and water resources. The participation of the wetland users is crucial for extenuating the problems related to wetland. This paper includes some ideas about community participation and role of local people in wetland conservation and management, reason for conservation of wetland sites, wetland policy based on local participation, and approaches for ensuring participation in wetland conservation programs. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 140-147 DOI: http://dx.doi.org/10.3126/aej.v12i0.7574